Hospital waste- Recycling for hospital energy feedback - Araujo, Eliete de Pinho; Lopes , Ingrid Christine da Silva Bastos; Domenech, Priscilla Benevides Segarra (Seven Editora, 2024)
Considering the view of hospital waste as dangerous and potentially infectious, the treatment given may be diffuse and inadequate. In this context, this work aimed to investigate the possibility of adapting recycling methods to various hospital waste, to generate energy to feed back the hospital building. Solid waste, especially health waste, is today a major pollutant of the environment and the legislation exempts the State from responsibility for its illegal disposal in common landfills. Hospital administrators may package and store in a way that does not consider the type of collection, transportation, treatment, and destination system. The current legislation lacks more in-depth research in the area to work in a more functional way and consider the possibility of recycling to generate products that can be used again, with minimal dumping and damage to the environment. Currently, hospital buildings do not have processes that enable total efficiency of their structure and ways to feed back into the building itself. It is still necessary, in most cases, to use extra power generators and dispose of water, garbage and other materials that can be reused. It was only in 2010 that the law establishing the National Solid Waste Policy was approved, after twenty years of discussions in the National Congress. This law establishes that environmental education is a fundamental instrument for success in this purpose of changing a culture in relation to waste disposal. In fact, garbage is a word that has already been proscribed by law, and today we speak of waste and rejects, because everyone should take advantage of this material. There is also a concern with improving the quality of life of human beings, the maintenance of life on the planet and the survival of the ecosystem. Doubts arise about what to do with the production and with what has already been produced of waste so that it does not cause further irreversible damage to the environment. It is these doubts that arose for the research theme. To support the answers to the questions raised in this study, the buildings of the Regional Hospital of Taguatinga (HRT - DF) and the Regional Hospital of Santa Maria (HRSM - DF) were studied, as references. Also the ENSP-FIOCRUZ Thesis, 2008 – Araujo, E. P. quality of life, clean energy production, necessary changes in legislation and their applications in architectural design. In the end, a booklet was prepared for the user campaign and an architectural project with the appropriate space in the hospital for the storage of the waste until the destination, thus being able, in various ways, to feed back into the building. DOI:https://doi.org/10.56238/sevened2023.004-062